Zawody piłkarskie Pomorzanin-Lechia. (Gdańsk : [s.n.], 1948)
Afisz inf. o meczu 07.08.1948 r.
Keywords: Lechia Gdańsk -- 1945-1970 -- druki ulotne; Piłka nożna -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne